In vivo expansion and regeneration of full‐thickness functional skin with an autologous homologous skin construct: Clinical proof of concept for chronic wound healing. Issue 3 (13th March 2019) - Granick, Mark S.; Baetz, Nicholas W.; Labroo, Pratima; Milner, Stephen; Li, William W.; Sopko, Nikolai A.
Abstract : A new cell‐tissue technology uses a patient's skin to create an in vivo expanding and self‐organising full‐thickness skin autograft derived from potent cutaneous appendages. This autologous homologous skin construct (AHSC) is manufactured from a small full‐thickness skin harvest obtained from an uninjured area of the patient. All the harvested tissue is incorporated into the AHSC including the endogenous regenerative cellular populations responsible for skin maintenance and repair, which are activated during the manufacturing process. Without any exogenous supplementation or culturing, the AHSC is swiftly returned to the patient's wound bed, where it expands and closes the defect from the inside out with full‐thickness fully functional skin. AHSC was applied to a greater than two‐year old large (200 cm 2 ) chronic wound refractory to multiple failed split‐thickness skin grafts. Complete epithelial coverage was achieved in 8 weeks, and complete wound coverage with full‐thickness functional skin occurred in 12 weeks. At 6‐month follow‐up, the wound remained covered with full‐thickness skin, grossly equivalent to surrounding native skin qualitatively and quantitatively equivalent across multiple functions and characteristics, including sensation, hair follicle morphology, bio‐impedance and composition, pigment regeneration, and gland production.